The First European Maps of Muscovy (1525) - O. F. Kudryavtsev (Vestnik MGIMO-Universiteta, 2020)
The earliest maps entirely or at least partially dedicated to Muscovy appeared in Europe in 1520s as a result of an increasing interest in this land. Around this time a famous Italian humanist Paolo Giovio promised in his book «Libellus de legatione Basilii magni Principis Moscouiae ad Clementem. VII. Pont. Max.» to reproduce a map of Muscovy in print (in tabula typis excusa). But the map didn’t appear either in the first nor in succeeding editions of the Giovio’s book.Nevertheless, the map was discovered even in two versions. The first was found in manuscript atlas made in the first half of the 16th century in Venice by cartographer from Genoa Battista Agnese. The second one is a printed map prepared, as it seems, by Paolo Giovio for his book but for some reasons not added to it. Both maps have much in common, as a kind of introduction to them serves almost the same inscription: «Moscoviae tabula relatione Dimetrij legati descrypta sicuti ipse a pluribus accepit, cum totam prouinciam minime peragrasse fateatur anno M.D.XXV. octobris».After examining the two earliest maps of Muscovy I can support the opinion already expressed in historiography that for their resemblance they might be the variants of the same map. Nevertheless, there are some important and obvious differences in location of geographical objects and their names, which are difficult to account for in case the one map is a reproduction of the other.The fact that the first two European maps of Muscovy appeared in autumn 1525 coinciding with publication of three books about this country written by Paolo Giovio, Albertus Campensis and Johann Fabri is indicative of a great and intense attention which Europe payed to Muscovy in its oriental boundaries around this time. These maps complement the descriptions of Muscovy in above mentioned books by giving detailed and visual representation of Muscovy land as a complicated geographical object. We must acknowledge their authors – in spite of a great number of mistakes – were able to cope with this task.